The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/toxins13080589
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Growth, Photosynthesis Performance, Pigments, and Toxin Contents of Bloom-Forming Cyanobacteria after Exposure to Macroalgal Allelochemicals

Abstract: Macroalgae can directly restrict the growth of various phytoplankton species by releasing allelopathic compounds; therefore, considerable attention should be paid to the allelopathic potential of these organisms against harmful and bloom-forming cyanobacteria. The main aim of this study was to demonstrate for the first time the allelopathic activity of Ulva intestinalis on the growth, the fluorescence parameters: the maximum PSII quantum efficiency (Fv/Fm) and the effective quantum yield of PSII photochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Jin et al (2005) investigated the inhibitory effect of fresh thallus and extract of U. pertusa and U. linza L. on the dinoflagellata Prorocentrum micans Ehrenberg. A recent work indicates that Ulva intestinalis L. also has allelopathic properties (Budzałek et al, 2021a). It was shown that the addition of the cell-free filtrate obtained from U. intestinalis significantly inhibited growth and photosynthetic efficiency of filamentous cyanobacteria Nodularia spumigena Mertens ex Bornet & Flahault and Nostoc sp.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Jin et al (2005) investigated the inhibitory effect of fresh thallus and extract of U. pertusa and U. linza L. on the dinoflagellata Prorocentrum micans Ehrenberg. A recent work indicates that Ulva intestinalis L. also has allelopathic properties (Budzałek et al, 2021a). It was shown that the addition of the cell-free filtrate obtained from U. intestinalis significantly inhibited growth and photosynthetic efficiency of filamentous cyanobacteria Nodularia spumigena Mertens ex Bornet & Flahault and Nostoc sp.…”
Section: Introductionmentioning
confidence: 99%